Promosi Kesehatan dengan Dukungan Kesehatan Jiwa Psikososial untuk Pencegahan Perilaku “Self Harm” pada Angkatan Muda Muhammadiyah melalui Pemberian Psikoterapi - Agustin, Ike Mardiati; Sumarsih, Tri; Qomar, Umi Laelatul (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The transition from adolescence to adulthood can lead to various emotional problems. Psychological issues in adolescents may include violent and spontaneous behavior, lack of focus, reduced interest in activities, symptoms of depression, and anxiety, often manifested in self-harming behavior. Adolescents, including those in the Muhammadiyah Youth Organization (Angkatan Muda Muhammadiyah), are also vulnerable to these problems despite the expectation to maintain good physical and psychological health. Therefore, preventive efforts are needed to address self-harm behavior using non-psychopharmacological approaches such as individual psychotherapy, namely Spiritual Emotional Freedom Technique (SEFT) and affirmations. Objective: To help overcome mental health problems in adolescents and prevent self-harm behavior through a psychotherapy program Method: The program was carried out in three stages: preparation through a pretest to assess adolescents’ anxiety, depression, and self-esteem; implementation of 45-minute therapy sessions using deep breathing, five-finger hypnosis, and butterfly hug affirmation techniques; and evaluation through a posttest using standardized questionnaires (HADS for anxiety and depression, and RSES for self-esteem). Data were analyzed descriptively to assess changes before and after the intervention. A psychotherapy program was implemented for 25 adolescents. The intervention consisted of 4 sessions, each lasting 45–60 minutes, conducted over a period of 1 month. The techniques used were SEFT and affirmations. Result: The program showed an increase in adolescents’ knowledge and psychomotor skills related to implementing psychotherapy when comparing pre- and post-training outcomes. Conclusion: This program is recommended as a preventive effort to address mental health problems and reduce the risk of self-harm behavior in adolescents.